Cover Picture: Reprogramming the Biosynthesis of Cyclodepsipeptide Synthetases to Obtain New Enniatins and Beauvericins (ChemBioChem 4/2016). (February 2016) - Zobel, Sophia; Boecker, Simon; Kulke, Daniel; Heimbach, Dirk; Meyer, Vera; Süssmuth, Roderich D.
Abstract : The cover picture shows the non‐ribosomally synthesized cyclodepsipeptides PF1022, beauvericin and enniatin with high pharmacological importance because of their various bioactivities. Today, PF1022 and derivatives are under trials for use for treatment of neglected diseases like filariasis, which is of considerable interest due to the more recent development of resistances against the anthelmintic avermectin. Based on the modular organization of NRPS we considered each module to be a piece of a jigsaw puzzle that can be replaced by the corresponding piece of a homologous NRPS enzyme: the first module of the PF1022 was exchanged for the respective module of the enniatin and beauvericin synthetases to create new‐to‐nature cyclodepsipeptides with promising bioactivities. We were able to express the different artificial NRPS enzymes of fungal origin in both, Escherichia coli and the filamentous fungus Aspergillus niger . An anthelmintic bioactivity assay revealed promising bioactivity against microfilariae of Dirofilaria immitis . More information can be found in the communication by R. D. Süssmuth et al. onpage 283 in Issue 4, 2016 (DOI:10.1002/cbic.201500649 ).